2018
DOI: 10.1002/adhm.201800673
|View full text |Cite
|
Sign up to set email alerts
|

Amnion‐Analogous Medical Device for Fetal Membrane Healing: A Preclinical Long‐Term Study

Abstract: Although recent invasive fetal surgeries have improved fetal outcomes, fetal membrane rupture remains a major complication, leading to premature delivery, thus undermining the complete benefits of such procedures. A biocompatible amnion-analogous medical device (AMED) consisting of polycaprolactone framework and decellularized amniotic membrane (dAM)-derived hydrogel for restoration of amniotic membrane defect is developed using 3D printing technology. Its efficacy on healing iatrogenic fetal membrane defects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…The collagen content of the decellularized hAM matrix was measured by a hydroxyproline assay kit (Cell Biolabs Inc) by following the vendor's protocol as previously described. [30] Briefly, hAM powder was hydrolyzed by 12N hydrochloric acid for 3 hours at 120º C to free hydroxyproline. The acid-hydrolyzed samples were further dried under vacuum evaporation at 80ºC for 40 minutes.…”
Section: Characterization Of Injectable Ham Matrixmentioning
confidence: 99%
“…The collagen content of the decellularized hAM matrix was measured by a hydroxyproline assay kit (Cell Biolabs Inc) by following the vendor's protocol as previously described. [30] Briefly, hAM powder was hydrolyzed by 12N hydrochloric acid for 3 hours at 120º C to free hydroxyproline. The acid-hydrolyzed samples were further dried under vacuum evaporation at 80ºC for 40 minutes.…”
Section: Characterization Of Injectable Ham Matrixmentioning
confidence: 99%
“…Recently, an amnion-analogous device (AMED) for the positioning of a 3D-printed medical device filled with a DAM-based solution in swine was developed. 106 The use of the device improved fetal survival rate and AF presence rates when compared to non-treated controls, but it was still lower than for intact FMs.…”
Section: Translational Strategies For the Prevention Of Ipprommentioning
confidence: 87%
“…Investigations with larger animals have included trials in swine, sheep and rhesus monkey. 106–109 Although they have longer gestational periods and are bigger in size, swine should be discarded in FM repair studies because the spontaneous healing of their FMs has been observed. 108 Sheep, on the other hand, would be more adequate models since they also have long gestational periods and a size that is almost directly translatable to humans.…”
Section: Translational Strategies For the Prevention Of Ipprommentioning
confidence: 99%
“…Although there have been significant advances in fetal diagnosis, the FMs are inevitably breached during fetal surgeries and therapies. 365 Previous studies have shown that the destruction of FMs cannot be healed entirely due to their largely avascular physiological state. 366,367 Therefore, the FM rupture makes fetal surgery extremely dangerous, and it is related to premature preterm rupture of membranes (PPROM) in some cases, which can lead to fetal death.…”
Section: Supramolecular Adhesive Hydrogels For Fetal Membrane Repairmentioning
confidence: 99%